2023
DOI: 10.1039/d2qo01783k
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed [4 + 2] cycloaddition of amido-tethered allylic carbonates with oxazol-5-(4H)-ones: synthesis of piperidine-2,6-dione derivatives

Abstract: A palladium-catalyzed [4+2] cycloaddition of amido-tethered allylic carbonates with oxazol-5-(4H)-ones proceeded smoothly under mild reaction conditions to give various piperidine derivatives in moderate to excellent yields. The reaction worked via...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Based on the experimental observations and previous literature, 6–13 a mechanism was proposed, as shown in Scheme 6. Under the catalysis of the PdL complex, the decarboxylation of sulfonamido-substituted acyclic allylic carbonates 2 results in aza-π-allylpalladium zwitterionic intermediates A along with the extrusion of CO 2 and t BuOH.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on the experimental observations and previous literature, 6–13 a mechanism was proposed, as shown in Scheme 6. Under the catalysis of the PdL complex, the decarboxylation of sulfonamido-substituted acyclic allylic carbonates 2 results in aza-π-allylpalladium zwitterionic intermediates A along with the extrusion of CO 2 and t BuOH.…”
Section: Resultsmentioning
confidence: 98%
“…Over the past few years, various precursors have been designed, synthesized and applied for different types of palladium-catalyzed decarboxylative chemical transformations. 6–13 Through in-depth literature research, it was found that the precursors to in situ form π-allylpalladium zwitterionic intermediates via a decarboxylation process mainly include cyclic vinyl carbonates, lactones and oxazolidin-2-ones (Scheme 1a), such as vinylethylene carbonates, 6 2-alkylidenetrimethylene carbonates, 8 γ-methylidene-δ-valerolactones, 9 vinyl benzoxazinones, 10 and vinyl methylene cyclic carbonates. 11 An alternative way for generating π-allylpalladium zwitterionic intermediates is to use acyclic allylic carbonates, and almost all studies focused on Pd-trimethylenemethane (TMM) zwitterionic intermediates containing a ligand-ligated π-allylpalladium cation and a carbanion counterpart (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%
“…In 2023, Wang with co-authors 40 published an article on the synthesis of glutarimides 40 by the reaction of tert-butyl (1-alkyl-2-(phenylcarbamoyl)hallel)carbonates 38 with 4-(alkyl)-2-aryloxazole-5(4H)-one 39. The reaction is car-ried out in a dichloromethane medium in a nitrogen atmosphere with catalysis from various diphenylphosphine derivatives and a palladium salt (Scheme 18).…”
Section: Scheme 16 Synthesis Of 4-aryl-3-methylidene Piperidine-26-di...mentioning
confidence: 99%
“…Based on these works involving VBLs, in order to synthesize biologically significant nine-membered heterocycles, we continued to explore Pd-catalyzed [5 + 4] cycloaddition of π-allyl-Pd all-carbon-1,5-dipoles from VBLs with azadienes, which is an effective four-atom unit for cycloaddition reactions owing to the driving force of aromatization . As our continuous efforts in cycloaddition reactions, we herein described a Pd-catalyzed [5 + 4] cycloaddition of VBLs with azadienes to afford an array of nine-membered aza-heterocycles (Scheme c).…”
Section: Introductionmentioning
confidence: 99%